“This course is like paying to volunteer” or is it? Effects of a Mandatory Service-Learning Course on Teacher Candidates - Sokal, Laura; Barrett, Vern; Appel, Allan; Funk, Anneke; Radawetz, Mykaila (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
One hundred teacher candidates enrolled in a mandatory course on service learning were surveyed pre- and post-course to determine their civic attitudes and willingness to take the service learning course. Quantitative analysis indicated significant growth in civic attitudes in all students, and this growth was not differentially affected by the students’ willingness to take the course. Qualitative data were analyzed to determine the underpinnings for students’ perceptions, and recommendations about the wisdom of making such courses mandatory in teacher preparation programs are provided.